Analisis Pengaruh Debt To Equity Ratio Dan Net Profit Margin Terhadap Harga Saham Pada PT. Bekasi Asri Pemula Tbk - Khalidah, Titin; Rimawan, M. (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
The property and real estate sector is one of the most important sectors in a country. With a large population in Indonesia and high economic growth in Indonesia, it creates a need for more effective and more efficient development in Indonesia. This research aims to determine the effect of Debt To Quity Ratio and Net Profit Margin on share prices at PT Bekasi Asri Pemula Tbk. This form of research is associative research. The object of this research is PT Bekasi Asri Pemula Tbk. The sampling technique in this research uses purposive sampling. The data analysis technique used is quantitative methods with descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, correlation and coefficient of determination as well as hypothesis testing in the form of T tests and F tests. The test results show that the Debt To Equity Ratio has a partially significant effect on stock prices, while Net Profit Margin does not have a partially significant effect on share prices